2009
DOI: 10.1002/stem.150
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Osteogenic Precursor Cells in Heterotopic Bone Formation

Abstract: Cells with osteogenic potential can be found in a variety of tissues. Here we show that circulating osteogenic precursor (COP) cells, a bone marrow-derived type I collagen+/CD45+ subpopulation of mononuclear adherent cells, are present in early pre-osseous fibroproliferative lesions in patients with fibrodysplasia ossificans progressiva (FOP) and nucleate heterotopic ossification (HO) in a murine in vivo implantation assay. Blood samples from FOP patients with active episodes of HO contain significantly higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
115
0
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 114 publications
(122 citation statements)
references
References 66 publications
4
115
0
3
Order By: Relevance
“…There is increasing evidence that COP cells participate in HO after hip arthroplasty, in end-stage aortic valvular disease, and in a genetic syndrome of extraskeletal bone formation. (16,62,63) Animal models of ectopic bone formation also support the notion of COP cell involvement in lesion formation. (12,13,16) In a rare genetic disorder of HO, FOP, patients with active episodes of extraskeletal bone formation have higher numbers of clonally derived COP cell colonies than patients with stable disease or unaffected individuals, and these COP cells are present in early fibroproliferative lesions.…”
Section: Possible Physiological and Pathological Functionsmentioning
confidence: 88%
“…There is increasing evidence that COP cells participate in HO after hip arthroplasty, in end-stage aortic valvular disease, and in a genetic syndrome of extraskeletal bone formation. (16,62,63) Animal models of ectopic bone formation also support the notion of COP cell involvement in lesion formation. (12,13,16) In a rare genetic disorder of HO, FOP, patients with active episodes of extraskeletal bone formation have higher numbers of clonally derived COP cell colonies than patients with stable disease or unaffected individuals, and these COP cells are present in early fibroproliferative lesions.…”
Section: Possible Physiological and Pathological Functionsmentioning
confidence: 88%
“…Given the known mechanism of action of BTxA (inhibition of neurotransmitter release), we therefore speculated that the blockade of neuromuscular signaling by BTxA inhibits neuromuscular interactions integral to the osteogenic response elicited by musculoskeletal trauma. Furthermore, because fracture healing and HO share common initiating events (including inflammation and BMP signaling) [17,27,30,32], we also speculated that BTxA-induced muscle paralysis would prevent the formation of heterotopic bone. However, interpreting the precise mechanism by which muscle paralysis inhibits osteogenesis in the rat fracture model is confounded by the heterogeneity of the tissue response, soft tissue injury, and modified gait kinematics, all of which can alter the observed cellular responses.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, two recent studies reported that aortic valve calcification is associated with ectopic ossification induced by various bone marrow-derived circulating osteogenic progenitor (COP) cells, such as type I collagen/CD45-positive and/or osteocalcin/CD45-positive cells [12,13]. However, whether these progenitor cells that reside in the aortic valve trigger valve calcification has yet to be confirmed.…”
Section: Introductionmentioning
confidence: 99%